PENERAPAN HEALING ENVIRONMENT PADA PERANCANGAN RSIA - Henry Soleman Raubaba; Muchlis Alahudin; Sari Octavia (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
Healing environment is one of the design concepts that prioritizes environmental factors because the environment plays animportant role in the healing and recovery process of humans in addition to medical, genetic and other factors. Applicationof the concept of healing environment in the design of the Maternal and Child Hospital (RSIA) in terms of architecture cancreate an ideal built environment and influence the psychology of space that helps mother and child patients adapt to therecovery process. The research method used is descriptive qualitative research method to describe and describe thephenomena that exist in the Maternal and Child Hospital, both natural and human engineering, which is more concernedabout the characteristics, quality and relationships between activities as well as the relationship with the application of theconcept of healing environment. The results showed that the Maternal and Child Hospital (RSIA) is not only a health carefacility for mothers and children, but also offers comfort and aesthetics in the design of the physical environment. Theapplication of the concept of healing environment in the Mother and Child Hospital combines natural, sensory andpsychological aspects that aim to support adaptation to the environment and the physical condition of the patient in therecovery process. The concept is applied to the design of the elements outside the building (exterior) and inside the building(interior) in the form of communicative circulation, the creation of a healing garden, structuring the building mass, goodlighting, utilization of the view, sound conditioning, and color play on the building.